2021
DOI: 10.3390/molecules26061791
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dual Drug Approach That Combines Ivermectin and Dihydromyricetin (DHM) to Reduce Alcohol Drinking and Preference in Mice

Abstract: Alcohol use disorder (AUD) affects over 18 million people in the US. Unfortunately, pharmacotherapies available for AUD have limited clinical success and are under prescribed. Previously, we established that avermectin compounds (ivermectin [IVM] and moxidectin) reduce alcohol (ethanol/EtOH) consumption in mice, but these effects are limited by P-glycoprotein (Pgp/ABCB1) efflux. The current study tested the hypothesis that dihydromyricetin (DHM), a natural product suggested to inhibit Pgp, will enhance IVM pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Additionally, Huang et al demonstrated that absorption of DHM was increased by the addition of verapamil, an inhibitor of P-glycoprotein (Pgp) efflux transporters [ 35 ]. This suggests that activity of Pgp transporters in the intestinal tract decreases DHM bioavailability and correlates with reports of DHM to act as a Pgp substate and inhibitor [ 36 , 37 ]. Interestingly, we found sex to have a significant influence on DHM serum exposure following PO, but not IP administration.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, Huang et al demonstrated that absorption of DHM was increased by the addition of verapamil, an inhibitor of P-glycoprotein (Pgp) efflux transporters [ 35 ]. This suggests that activity of Pgp transporters in the intestinal tract decreases DHM bioavailability and correlates with reports of DHM to act as a Pgp substate and inhibitor [ 36 , 37 ]. Interestingly, we found sex to have a significant influence on DHM serum exposure following PO, but not IP administration.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, DHM can inhibit ROS accumulation through pGC-1α/SIRT3 signal pathway and protect cells from apoptotic cell death, thus preventing hearing loss caused by oxidative damage of auditory hair cells (Han et al., 2020 ). DHM can also reverse the reduced bioavailability of ivermectin (IVA) due to the presence of P-glycoprotein, which is an innovative therapy for alcohol use disorder and secondary alcoholic liver disease (Silva et al., 2021 ). Moreover, the use of DHM as an adjunct to BACE1 inhibitors in the treatment of Alzheimer’s disease (AD) can reduce the cross-inhibitory toxicity of BACE1 inhibitors, and can delay or reverse the AD progression (Das et al., 2020 ).…”
Section: Pharmaceutical Designs For the Combined Application Of Dhm W...mentioning
confidence: 99%
“…It also has effects on nonalcoholic fatty liver disease, aging-related tissue fibrosis, metabolic syndrome, diabetes and diabetic complications, inflammation-induced muscle atrophy, Alzheimer’s disease, etc. It is known that DHM inhibits dihydropyrimidinase (with an IC 50 of 48 μM, antibacterial activity), p-glycoprotein ATPase, SIRT1, and GRP78 in vitro studies. Those targets have not been verified in vivo .…”
Section: Challenges and Perspectivementioning
confidence: 99%